PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA PROGRAM INDIHOME TRIPLE PLAY PT. TELKOM (CABANG PLASA MEDAN) - Kristi Endah Ndilosa Ginting; Deni Faisal Mirza; Adinda Tri Adelia Putri; Desi Widiyanti Brutu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2021)
The research objectives were to test and analyze the effect of price and quality of service on customers’ satisfaction at PT. Telkom (Plasa Telkom Branch Medan). The researcher conducted the research at PT. Telkom (Plasa Telkom Branch Medan) in Medan, North Sumatra. The researcher planned research activities in April 2019 - September 2019. The approach of this research was quantitative research. The type of research was quantitative descriptive research. The nature of this research was explanatory descriptive research. The population in this study was some customers at PT. Telkom (Plasa Telkom Branch Medan), as many as 5219 customers. The population in this study was some customers who made purchases at PT. Telkom (Plasa Telkom Branch Medan) as many as 5219 customers. In testing the validity and reliability, the researcher used as many as 30 customers and the rest 98 customers as sample test. The regression model was used to test the hypothesis. First the model was tested in the classical assumption. The classical assumption tests used included: normality test, multicollinearity test and heteroscedestity test. The data analysis model used was multiple regression analysis. The results of the study as well as the conclusions of the study were the prices of 5.936 with a significant value of 0.003 partially had significant effect on customers’ satisfaction at PT. Telkom (Plasa Telkom Branch Medan). Service Quality was 2.201 with a significant value of 0.030 partially had significant effect on customers’ satisfaction at PT. Telkom (Plasa Telkom Branch Medan).